Manajemen Terpadu Budidaya Kale dalam Rumah Kaca untuk Meningkatkan Kualitas, Produktivitas, dan Nilai Ekonomi - Hanaa Hafizhah; Muhamad Fadhilah Yahya; Lulu Dwi Ghania; Syifa Maharani; Neila Maulidya; Dwi Kartika Andini; Nisrina Nasila Anbarwati; Haidar Dhiya Razzan; Agief Julio Pratama; M. Iqbal Nurulhaq; Ririh Sekar Mardisiwi; Ratih Kemala Dewi; Restu Puji Mumpuni; Edi Wiraguna (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2026)
Postharvest handling of leafy vegetables, such as kale (Brassica oleracea var. acephala), is crucial for maintaining product quality and market value. This study aims to review the application of sorting and grading processes in improving the quality of horticultural products. The method used is a literature review of scientific journals and relevant references related to postharvest handling of vegetables. The findings indicate that sorting functions to separate damaged and unmarketable products based on physical condition, while grading classifies products into quality categories based on size, shape, and visual appearance. These processes contribute to reducing postharvest losses, improving product uniformity, and increasing market value. Furthermore, proper sorting and grading support quality control and enhance efficiency in distribution and marketing systems. Therefore, sorting and grading are essential components of postharvest management to ensure product quality and market competitiveness.